Analysis and Design of Discrete Part Production Lines - Papadopoulos, Chrissoleon T.; O'Kelly, Michael E. J.; Vidalis, Michael J.; Spinellis, Diomidis (Springer Optimization and Its Applications, 2009)
Analysis and Design of Discrete Part Production Lines provides a complete overview of production systems, investigating several production line problems, and describing the best approaches to the analysis of production line performance. Written by experts in the field of production and manufacturing research, this book also presents numerous techniques that can be used to describe and model various types of production lines. Special Features: * Includes access to a supplementary web-based software package, providing algorithms and examples, developed by distinguished experts of the field. * Describes new results for evaluative techniques and design algorithms as well as several open problems in production line optimization. * Presents in detail the theory and techniques that underlie production system management, design, and analysis, allowing the book to serve as an excellent introduction to newcomers in the field. * Has potential for use in a graduate level course in industrial or manufacturing engineering, or in a business course with a manufacturing focus. * Contains appendices providing an overview of several mathematical techniques employed to design and evaluate production line models. This book is intended for researchers, production managers, and graduate students in industrial, mechanical, and systems engineering. Using the resources presented, consultants, engineers, and researchers will be able to design, evaluate, determine the behavior, and optimize the performance of both new and existing production lines.